2002
DOI: 10.1159/000048646
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Two Telephone Screens for Cognitive Impairment

Abstract: We studied 56 subjects, 30 patients with a clinical diagnosis of Alzheimer’s disease (AD) and 26 healthy controls, using two telephone screens for cognitive impairment, a self-report interview referred to as the TELE and the Telephone Interview for Cognitive Status (TICS). The sensitivity and specificity of the TELE to differentiate AD patients from healthy controls was 90.0 and 88.5% and those of the TICS were 86.7 and 88.5%, respectively. When receiver operator characteristic curves were constructed, the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 11 publications
(21 reference statements)
3
83
0
Order By: Relevance
“…Sensitivity and specificity was distinguished between AD and CTL. The cutoff score for the TICS-J was higher than in previous studies (Brandt et al, 1988;Mangione et al, 1993;Desmond et al, 1994;Ferrucci et al, 1998; Järvenpää et al, 2002;Barber and Stott, 2004). Subjects in CTL were urban residents and well educated with an active social life which may be lead to the high cutoff points for the TICS-J and the MMSE.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Sensitivity and specificity was distinguished between AD and CTL. The cutoff score for the TICS-J was higher than in previous studies (Brandt et al, 1988;Mangione et al, 1993;Desmond et al, 1994;Ferrucci et al, 1998; Järvenpää et al, 2002;Barber and Stott, 2004). Subjects in CTL were urban residents and well educated with an active social life which may be lead to the high cutoff points for the TICS-J and the MMSE.…”
Section: Discussionmentioning
confidence: 63%
“…The TICS has been translated into several foreign languages, including Spanish (Desmond et al, 1994;Gude Ruiz et al, 1994), Italian (Ferrucci et al, 1998) and Finnish (Järvenpää et al, 2002). Japanese language, including the culture, the social systems and education is quite different from the languages and cultures of countries of Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The initial discordance of the twin pairs for dementia was based on the scores received from the TELE [26], a telephone interview assessing cognitive status. Earlier research has shown that it is a sensitive and specific instrument for differentiating AD patients from healthy controls [26,27]. After this initial telephone screen, the discordance of the twins was confirmed with a detailed neuropsychological investigation.…”
Section: Discussionmentioning
confidence: 82%
“…For this purpose, we examined 7 pairs of monozygotic twins discordant for AD. These twins were screened from a nationwide twin panel [25] using a sensitive and specific telephone screen, which has previously been successful in the differentiation of AD patients from healthy controls [26,27]. Their discordance was confirmed with a detailed neuropsychological investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Tools to measure memory impairment objectively are plentiful and usually include a subset of questions related to overall cognitive function; examples are the Mini-Mental State Exam (MMSE) (Folstein et al 1975), Hodkinson's 10-item Abbreviated Mental Test (Hodkinson 1972, Saraquesta et al 2001, the Seven-minute Neurocognitive Screening Battery (Solomon et al 1998, Ellis 2004, Sood et al 2004) and the 6 Item Cognitive Impairment Test (6CIT) (Brooke & Bullock 1999). The specific cognitive domain of memory alone has been screened for using telephone interviews with the Memory Impairment Screen for Telephone tool and the Telephone Interview for Cognitive Status (TICS) tools (Jä venpä ä et al 2002, Chodosh et al 2007). However, simply ruling out memory loss associated with cognitive impairment does not address other pathological causes of forgetfulness in older adults (Bä ckman et al 2004).…”
Section: Introductionmentioning
confidence: 99%